The association of male pattern baldness and risk of cancer and high-grade disease among men presenting for prostate biopsy - Al Edwan, Ghazi (Can Urol Assoc J, 2016)
INTRODUCTION: Androgens have been implicated in both male pattern baldness (MPB) and prostate cancer (PCa). We set out to prospectively determine if men with independently assessed MPB are at higher risk for PCa at biopsy and determine if any grade associations exist. METHODS: We prospectively enrolled 394 eligible patients presenting for prostate biopsy and independently determined their MPB pattern using the validated modified Norwood classification system (0: no balding; 1: frontal balding; 2: mild vertex balding; 3: moderate vertex balding; 4: sever vertex balding). Univariate and multivariable models, including Norwood score, age, prostate-specific antigen, and digital rectal examination abnormalities, were calculated for the outcomes of cancer and high-grade disease (Gleason >6). C-statistics analyses of our models were then compared with and without MPB pattern for marginal utility. RESULTS: Norwood patterns were increasingly associated with cancer and high-grade disease with a dose-effect (p for trend <0.001 on univariate and multivariable analyses for cancer and p=0.001 and p=0.0036 for high-grade disease on univariate and multivariable analyses, respectively). On multivariable analyses, trends still held, with all patients exhibiting Norwood scale 3 and 4 at increased risk for cancer. In predicting risk of high-grade disease, only patients with Norwood pattern 4 exhibited an increased risk. CONCLUSIONS: MPB appears to be a strong and independent risk factor for both cancer and high-grade disease for men presenting for prostate biopsy. Ours could be superior to marketed costly genetic tests. Further research is needed to understand the biology behind this observation and to incorporate these findings into clinical decision-making.